Fluoride Level of Well Water and Dental Caries Status of Children in Surabaya - Sunomo Hadi; Jumriani Jumriani (Alliance oh Health Activists (AloHA), 2019)
Dental caries is a dental hard tissue disease that attacks almost all people in the world. Fluoride in water is very important for dental health, especially for children, this is because the right amount of intake can support the formation of tooth enamel that is resistant to damage caused by mouth. This study aims to determine the correlation of fluoride level in well water with the number of dental caries in elementary school children in the city of Surabaya in 2017. This research was analytic observational with a cross-sectional approach, located in four State Primary Schools in Surabaya City, representing North Surabaya, East Surabaya, South Surabaya and West Surabaya. The mean value of DMF-T of the study subjects was 1.58 (low category), the mean fluoride level in well water was 0.457 mg / L (low category). The results showed that the presence of fluoride in well water did not contribute to the low DMF-T value in this study. Keywords: Caries status, Well water, Fluoride levels